Association of eNOS Gene Polymorphisms G894T and T-786C with Risk of Hepatorenal Syndrome - Yuksel Seckin; Ali Yigit; Elif Yesilada; Gonca Gulbay; Yasir Furkan Cagin; Harika Gozukara; Yılmaz Bılgıc; Oguzhan Yildirim; Yusuf Turkoz; Zeynep Aksungur (Gastroenterology Research and Practice)
Background. There are no studies investigating the relationship between endothelial nitric oxide synthase (eNOS) gene polymorphisms and hepatorenal syndrome (HRS). Aim. The purpose of this study is to elucidate whether eNOS gene polymorphisms (G894T and T-786C) play a role in the development of type-2 HRS. Methods. This study was carried out in a group of 92 patients with cirrhosis (44 patients with type-2 HRS and 48 without HRS) and 50 healthy controls. Polymorphisms were determined by polymerase chain reaction (PCR) and melting curve analysis. Results. We did not find any significant difference in allele and genotype distributions of the eNOS -T-786C polymorphism among the groups (p=0.440). However, the frequency of GT (40.9%) and TT (13.6%) genotypes and mutant allele T (34.1%) for the eNOS G894T polymorphism were significantly higher (p<0.001 and p<0.001, resp.) in the HRS group than in both the stable cirrhosis (14.6%, 4.2%, and 11.5%, resp.) and the control (22.0%, 2.0%, and 13.0%, resp.) groups. Conclusion. The occurrence of mutant genotypes (GT/TT) and mutant allele T in eNOS -G894T polymorphisms should be considered as a potential risk factor in cirrhotic patients with HRS.